Proceedings of the 2nd International Conference on Natural Products for Cancer Prevention and Therapy 2017
DOI: 10.3390/proceedings1101071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant and Cytotoxic Activity of Known Antioxidants Compared to Neopterin

Abstract: Free radicals and other reactive oxygen species (ROS) are constantly formed in the human body. Free-radical mechanisms have been implicated in the pathology of several human diseases. Free radicals are generated physiologically during immune activation. Neopterin, an early marker of immune activation is released from monocyte-macrophages with the induction of interferon-gamma. Its biological levels are known to be increased in different types of pathologies including cancer. Neopterin is also known to be relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, antioxidants, like vitamins C, D and E may attenuate Covid-19 severity through modulation of glutathione level, immune response and tissue oxygenations [ 48 ]. It has been documented that NPT and 7,8-dihydro-NPT have antioxidant effects comparable to that of melatonin [ 49 ]. Similarly, high NPT level reflects a poor endogenous antioxidant capacity and deregulated immune response [ 50 ]; herein, NPT may attenuate Covid-19-associated inflammatory and OS-derived disorders as well as tissue damage (Fig.…”
Section: Role Of Neopterin In Covid-19mentioning
confidence: 99%
“…Thus, antioxidants, like vitamins C, D and E may attenuate Covid-19 severity through modulation of glutathione level, immune response and tissue oxygenations [ 48 ]. It has been documented that NPT and 7,8-dihydro-NPT have antioxidant effects comparable to that of melatonin [ 49 ]. Similarly, high NPT level reflects a poor endogenous antioxidant capacity and deregulated immune response [ 50 ]; herein, NPT may attenuate Covid-19-associated inflammatory and OS-derived disorders as well as tissue damage (Fig.…”
Section: Role Of Neopterin In Covid-19mentioning
confidence: 99%
“…The effects of neopterin are not yet fully elucidated. Still, studies indicated a link between neopterin and oxidative stress, with the formation of reactive oxygen species [ 12 ] known to play an essential role in the initiation, proliferation, and development of cancer cells by maintaining their survival [ 13 ]. The serum values of neopterin showed limited performance as a marker for CRC compared to CEA (CarcinoEmbryonic Antigen), TPA (tissue plasminogen activator), and CA 19/9 (cancer antigen 19-9) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%